Pattern of Congenital Heart Disease in Children Admitted into Tertiary Care Hospitals of Sylhet: A Multicenter Study (Bangladesh Journal of Child Health, 2014)
Objective: This study was carried out to find out the prevalence of CHD and their type among Children attended in the inpatient and out patient department of district tertiary care hospital of Sylhet. Methodology: This prospective cross sectional study was carried out in the department of Paediatrics of 4 medical college hospitals of Sylhet over a period of 1 year from January 2012 to December 2012. All children with the confirmed diagnosis of CHD with the age ranging from 1st day of life to 12 years were analyzed considering the pattern of CHD. Results: A total of 234 cases of CHD were admitted. Maximum cases of CHD were admitted between 29 days to 1year age group and 148 (63.25%) were male and the rest 86 (36.75%) were female. The male-female ration was 1.72:1. Most of the CHD (65.38%) were acyanotic and 34.42% cases were cyanotic. The commonest CHD was found VSD (33.33%) which was followed by ASD (16.24%), TOF (11.54%), Complex CHD (11.54%) and PDA (10.68%). Conclusion: It was concluded from this study that the male children are mostly sufferer from CHD and acyanotic heart disease was commonest type of CHD. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20022 Bangladesh J Child Health 2014; VOL 38 (1) : 15-18